2006
DOI: 10.1542/peds.2006-0557
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Acute Renal Failure: 22-Year Experience in a University Hospital in Southern Thailand

Abstract: The incidence of acute renal failure in Songklanagarind Hospital was 0.5 to 9.9 cases per 1000 pediatric patients, with a mortality rate of 41.5%. Sepsis was a major cause of acute renal failure and death. Causes of acute renal failure and serum creatinine levels were significant independent predictors of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
107
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 17 publications
18
107
1
3
Order By: Relevance
“…incidences; rates of 17.9%-52% have been seen in the ICU or after corrective cardiac surgery (5,9,32). However, our findings are comparable with those findings of a single-center study, which used similar diagnostic criteria (4.6-9.9 per 1000 hospitalizations) (2). The large scale of our study allowed identification of novel AKI demographics in children.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…incidences; rates of 17.9%-52% have been seen in the ICU or after corrective cardiac surgery (5,9,32). However, our findings are comparable with those findings of a single-center study, which used similar diagnostic criteria (4.6-9.9 per 1000 hospitalizations) (2). The large scale of our study allowed identification of novel AKI demographics in children.…”
Section: Discussionsupporting
confidence: 85%
“…Most pediatric studies have been from single centers and are limited by small sample size and a propensity to focus only on critical care populations or children who require dialysis (2,(14)(15)(16)(17)(18)(19)(20)(21)(22). Studies have suggested that the epidemiology of pediatric AKI has changed dramatically over the past few decades, noting that sepsis, congenital heart disease, and oncologic illness have replaced hemolytic uremic syndrome, GN, and primary renal diseases as the most common causes of AKI in hospitalized children (14,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The incidence of AKI is high and continues to increase, 2,[5][6][7] which may lead to increasing prevalence of CKD, which in turn could create long-term burdens on patients and health care systems.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…Whereas in developed regions elderly patients predominate (4,5), in developing countries, AKI is a disease of the young (14,17,18) and children (19,20), in whom volume-responsive "prerenal" mechanisms are common (21)(22)(23)(24). Although overall mortality seems to be lower than in developed countries (25)(26)(27)(28), this finding is not true across all age groups: In these regions, AKI affects predominantly the young and children and mortality is high (29,30).…”
mentioning
confidence: 99%